Mixed messages - Wells, Tina, 1980- (Mackenzie Blue, 2010)
Mackenzie and her friends create a new online social networking site which creates some unforeseen problems, as she is also trying to figure out if she has a crush on one of her best friends, how to deal with the jealousy of one of her bandmates and her fears over her mother's pregnancy.